Experimental Investigation into the Effects of Fuel Dilution on the Change in Chemical Properties of Lubricating Oil Used in Fuel Injection Pump of Pielstick PA4 V185 Marine Diesel Engine - Piotr Kaminski (Lubricants, 2022)
The engine oil contamination caused by various chemical elements and fuel is an important problem. As a consequence, the engine oil loses its tribological properties, engine lubrication worsens and may lead to potential problems such as excessive wear, corrosion, etc. For that reason, the study of oil degradation and contamination due to the replacement strategies is of special interest to the engine operators and engine manufacturers. In this paper, the chemical elements and fuel dilution of engine oil are analyzed under real engine operating conditions. This research is focused on the fundamental question: how is the chemical performance of lubricant components impacted by diesel dilution? Various tribological tests were performed on regularly collected samples from the fuel injection pump of a Pielstick PA4 V185 marine diesel engine. These tests assessed the influence of fuel on the lubricating oil chemistry performance and useful residual life. Tests included variations in lubricant density, viscosity, flash point temperature and chemical components for 10 samples taken in the following hours of engine operation. Results suggest that diesel dilution only slightly affects chemical additive performance. Most of the examined chemical elements remained at a negligible level (below 1 ppm) in the case of elements whose content was greater, and the changes were either negligible (Al, Fe, MG, Si) in the grits from 1 to 5 ppm or higher (Ca, P, Zn, C), ranging from tens to several hundred ppm. On the other hand, the kinematic viscosity changed significantly from 89.8 to 12.0 cSt at 40 °C or from 9.8 to 2.9 cSt at 100 °C. The change in flash point, although significant from 236 (for fresh oil) to a value below 100, does not exceed the limit values. To sum up, the study concluded that the reduction in oil change intervals for this engine is worth considering under the given operating conditions.